Functional and Genome Sequence-Driven Characterization of tal Effector Gene Repertoires Reveals Novel Variants With Altered Specificities in Closely Related Malian Xanthomonas oryzae pv. oryzae Strains - Doucouré, Hinda; Pérez-Quintero, Alvaro L.; Reshetnyak, Ganna; Tekete, Cheick; Auguy, Florence; Thomas, Emilie; Koebnik, Ralf; Szurek, Boris; Koita, Ousmane; Verdier, Valérie; Cunnac, Sébastien (Frontiers in Microbiology, 2018)
Rice Bacterial Leaf Blight (BLB) is caused by Xanthomonas oryzae pv. oryzae (Xoo) which injects Transcription Activator-Like Effectors (TALEs) into the host cell to modulate the expression of target disease susceptibility genes. Xoo major-virulence TALEs universally target susceptibility genes of the SWEET sugar transporter family. TALE-unresponsive alleles of OsSWEET genes have been identified in the rice germplasm or created by genome editing and confer resistance to BLB. In recent years BLB has become one of the major biotic constraints to rice cultivation in Mali. To inform the deployment of alternative sources of resistance in this country, rice lines carrying alleles of OsSWEET14 unresponsive to either TalF (formerly Tal5) or TalC, two important TALEs previously identified in West African Xoo, were challenged with a panel of strains recently isolated in Mali and were found to remain susceptible to these isolates. The characterization of TALE repertoires revealed that talF and talC specific molecular markers were simultaneously present in all surveyed Malian strains, suggesting that the corresponding TALEs are broadly deployed by Malian Xoo to redundantly target the OsSWEET14 gene promoter. Consistent with this, the capacity of most Malian Xoo to induce OsSWEET14 was unaffected by either talC- or talF-unresponsive alleles of this gene. Long-read sequencing and assembly of eight Malian Xoo genomes confirmed the widespread occurrence of active TalF and TalC variants and provided a detailed insight into the diversity of TALE repertoires. All sequenced strains shared nine evolutionary related tal effector genes. Notably, a new TalF variant that is unable to induce OsSWEET14 was identified. Furthermore, two distinct TalB variants were shown to have lost the ability to simultaneously induce two susceptibility genes as previously reported for the founding members of this group from strains MAI1 and BAI3. Yet, both new TalB variants retained the ability to induce one or the other of the two susceptibility genes. These results reveal molecular and functional differences in tal repertoires and will be important for the sustainable deployment of broad-spectrum and durable resistance to BLB in West Africa.